PROCEDURAL PROBLEMS OF FORENSIC MEDICAL EXAMINATION OF THE CORPSE AND WAYS OF THEIR SOLUTION USING X-RAY METHOD OF COMPUTER TOMOGRAPHY - Andrey Anatolyevich Strelkov; Vladimir Kadyrovich Dadabaev (Гуманитарные и юридические исследования)
The article deals with procedural problems relating to the setting and conducting a forensic medical examination of a corpse. The authors analyse the possibility of their solution as a method of preliminary forensic examination through the usage in forensic practice innovative scientific-practical tech-niques of non-invasive (without the use of abdominal dissection of the body) ways of au-topsy - “virtual” autopsy carried out with the use of x-ray method of computed tomography (CT) and 3-D technologies.